Whole-genome analysis of Bacillus subtilis G8 isolated from natto - DIKSON DIKSON; HANS VICTOR; DELVIN JONG; ASTIA SANJAYA; ARIELA SAMANTHA; JUANDY JO; REINHARD PINONTOAN (Society for Indonesian Biodiversity, 2022)
Abstract. Dikson, Victor H, Jong D, Sanjaya A, Samantha A, Jo J, Pinontoan R. 2022. Whole-genome analysis of Bacillus subtilis G8 isolated from natto. Biodiversitas 23: 1293-1300. Bacillus subtilis-fermented soy-based food is associated with multiple health benefits. Various bacterial strains have been isolated from it, includingB. subtilisG8, recent isolation from Japanese natto commercially available in Indonesia. Both 16S rRNA gene sequencing and fibrinolytic activity characterization have been performed and published in prior studies. After comparison to the genome of a natto-isolated reference strain (i.e., B. subtilisBEST195), the B. subtilis G8 genome showed a similar guanine-cytosine (GC) content, predicted number of coding sequences (CDS) and predicted number of tRNA genes, but had a shorter sequence length and fewer predicted rRNA genes. Further analysis using multiple genome alignment with Mauve, average nucleotide identity (ANI) matrix calculation, and phylogenetic inference indicated that B. subtilis G8 was more related to natto-derived B. subtilis than to cheonggukjang-derived B. subtilis and B. subtilis 168. Finally, sequence analyses of a gene encoding nattokinase as well as two genes regulating poly-gamma-glutamic acid (?-PGA) production in B. subtilis G8, B. subtilis BEST195 and B. subtilis 168 clearly indicated that B. subtilis G8 is able to produce nattokinase and ?-PGA, which both contribute to natto’s fermentation process. Therefore, it is proposed that B. subtilis G8 should be reclassified as B. subtilis subsp. natto G8 to reflect that it is a natto-derived B. subtilis strain.